AB0765 Quality of life and fatigue in patients with behcet's disease. (23rd January 2014) - Can, M.; Alibaz-Öner, F.; Ilhan, B.; Öner, S.; Inanc, N.; Ergun, T.; Mumcu, G.; Direskeneli, H.
Abstract : Background: Behcet's disease (BD) is a multi-systemic, chronic inflammatory disorder characterized by vasculitis. Fatigue, a common symptom of inflammatory rheumatological disorders such as systemic lupus erythematosus (SLE) and vasculitides, is insufficiently studied in BD. Objectives: We aimed to assess fatigue in BD, comparing it with other patient-reported outcomes such as disability, quality of life (QoL) and anxiety/depression in this study. Methods: Fifty-one patients followed as BD (F/M:32/19, mean age: 39.4 years) fullfilling the International Study Group Criteria (ISG, 1990), 24 patients with SLE (F/M:23/1, mean age: 46.5 years) and 31 healthy controls (HC) (F/M: 24/7, mean age: 37.8 years) were enrolled to the study. The clinical activity score in BD was determined by Behcet's Syndrome Activity Scale (BSAS) and in SLE by SLEDAI. All subjects were asked to complete the Multi-dimensional assessment of fatigue (MAF) questionnaire. SF-36 and hospital anxiety and depression scales were also used to assess QoL together with health assessment questionnaire (HAQ). Results: Mean fatigue score was similar among the three groups [22.6 (15.3), 26.6 (10.9) and 24.1 (11.8) in BD, SLE and HC respectively] (p=0.4). When BD patients were separately analysed in 2 groups (mucocutaneous (MC) (n=17) and major organ involvement (MO) (ocular, vascular and central nervous system) (n=21)), fatigue score was also not different among both groups [22.3(17.7) vs 21.2(17.0), MC and MO respectively]. However, BSAS score was observed to correlate with the fatigue score (r=0.5, p=0.001).HAQ scores were impaired in BD and SLE patients compared to HC [0.32(0.42), 0.42(0.36) and 0.07 (0.1), respectively] (p<0.01). Anxiety [6.6 (4.2), 7.5 (4.1) and 6.0 (4.6) in BD, SLE and HC, respectively) (p>0.05), and depression scores were similar [6.3 (4.1), 7.2 (3.1) and 5.8 (3.5) in BD, SLE and HC respectively] (p>0.05) among the 3 groups. In subgroup analysis, SF-36 mental and physical components, depression and anxiety scores and HAQ were also not different between MC and MO groups. Conclusions: Contrary to previous studies, in this hospital-based, observational cohort study, fatigue seems to be similar in magnitude in BD compared to SLE and HC. Although major organ involvement did not affect fatigue severity, an association of fatigue with disease activity is observed. Disclosure of Interest: None Declared